Skin Mast Cells Contribute to Sporothrix schenckii Infection - Jiao, Qingqing; Luo, Ying; Scheffel, Jörg; Geng, Peng; Wang, Yuhan; Frischbutter, Stefan; Li, Ruoyu; Maurer, Marcus; Zhao, Zuotao (Frontiers in Immunology, 2020)
Background Sporothrix schenckii (S. schenckii), a dimorphic fungus, causes sporotrichosis. Mast cells (MCs) have been described to be involved in skin fungal infections. The role of MCs in cutaneous sporotrichosis remains largely unknown. Objectives To characterize the role and relevance of MCs in cutaneous sporotrichosis. Methods We analyzed cutaneous sporotrichosis in wild-type (WT) mice and two different MC-deﬁcient strains. In vitro, MCs were assessed for S. schenckii-induced cytokine production and degranulation after incubation with S. schenckii. We also explored the role of MCs in human cutaneous sporotrichosis. Results WT mice developed markedly larger skin lesions than MC-deficient mice (> 1.5 fold) after infection with S. schenckii, with significantly increased fungal burden. S. schenckii induced the release of tumor necrosis factor alpha (TNF), interleukin (IL)-6, IL-10, and IL-1β by MCs, but not degranulation. S. schenckii induced larger skin lesions and higher release of IL-6 and TNF by MCs as compared to the less virulent S. albicans. In patients with sporotrichosis, TNF and IL-6 were increased in skin lesions, and markedly elevated levels in the serum were linked to disease activity. Conclusions These findings suggest that cutaneous MCs contribute to skin sporotrichosis by releasing cytokines such as TNF and IL-6.